Thermo‐Kinematic Evolution of the Eastern European Alps Along the TRANSALP Transect. Issue 4 (12th April 2023) - Eizenhöfer, Paul R.; Glotzbach, Christoph; Kley, Jonas; Ehlers, Todd A.
Abstract: The eastern European Alps are shaped by the indentation of Adria into Europe. Recent tomography, depicting detached slab fragments, has been interpreted as evidence of continuous southward subduction of European lithosphere, contrary to an often‐invoked subduction polarity reversal. Orogen‐scale exhumation, driven by rock displacement along active faults, may reflect subduction polarity within the framework of doubly‐vergent Coulomb wedge theory, provided the absence of rheological contrasts across the colliding plates. Low‐temperature thermochronology can evaluate crustal cooling in response to changes in tectonic and erosional boundary conditions. This study investigates the consistency of observed crustal re‐organization, exhumation, and mantle processes in the Eastern Alps. Thermo‐kinematic forward models driven by reconstructions of crustal shortening along the TRANSALP geophysical transect were subjected to variations in shortening rates, thermophysical parameters, and topographic evolution, supplemented by new fission‐track data. The thermo‐kinematic models reproduce: (a) the orogen‐scale structural geometry, (b) the distribution of thermochronometer ages, (c) observed time‐temperature paths, and (f) the present‐day surface heat flux. Results suggest that exhumation is driven by rock displacement along active faults without the need to involve mantle‐driven buoyancy forces. Taken together, the results identify two possible scenarios: if the Tauern Ramp is a retro‐thrust and the southward shift of deformation in the Southern Alps is a response to new Coulomb‐wedge conditions, then our results support a Mid‐Miocene reversal of the subduction polarity. Alternatively, crustal deformation does not reflect mantle processes entailing a high degree of inter‐plate decoupling. Plain Language Summary: The convergence between the African and Eurasian plates created the European Alps. This process led to the Eurasian plate underlaying the African plate. It has been argued that this tectonic geometry changed, that is, Adria underlies Europe at present. Here we investigate whether changes in erosion and cooling of the crust over geologic time along a north‐to‐south profile in the Eastern Alps during the collision reflects deep seated mantle processes given the absence of rheological contrasts across the involved tectonic plates. New models for the structural and thermal evolution of the crust along the profile reproduce present‐day structural and thermal observations. Model predictions are sensitive to heat production in the crust. Furthermore, these models indicate that cooling of the crust through erosion was primarily driven by the displacement of rocks toward the surface along active faults. Two possible tectonic scenarios are suggested: The pattern of fault activity during the collision is characteristic for an overlying European plate promoting that now the Adriatic plate lies under the European plate. If this is the case, this change in tectonic geometry likely occurred about 10–20 million years ago. Alternatively, crustal deformation does not reflect mantle processes because the interface between the two colliding plates is highly decoupled along the profile. Key Points: Exhumation in the eastern European Alps along TRANSALP is primarily driven by cooling through rock displacement along active faults The thermo‐kinematic reconstruction emphasizes contrasts in the deformation north and south along TRANSALP since the Mid‐Miocene In the absence of inter‐plate rheological contrasts deformation patterns favor a reversal in subduction polarity since the Mid‐Miocene